9 Stat. at Large of Pa. 91, ch. 750, § 32, pt. 9 (1903) - (:unkn) unknown (My University, 1777)
Any officer or private man found drunk when under arms, shall be suspended from doing duty in the battalion, company or troop on that day, and be fined at the discretion of a General or Regimental Court-Martial.
Keywords: POSSESSION - DANGEROUS PERSONS